The Impact of COVID-19 Pandemic on Cleft Care Services at a Tertiary Health Facility in Nigeria. (December 2021) - Sabo, Vinishe Y.; James, Olutayo; Adamson, Olawale O.; Otoghile, Bright; Adeyemo, Wasiu L.; Ladeinde, Akinola; Ogunlewe, Mobolanle O.
Background: This study assessed the impact of COVID-19 Pandemic on cleft care services at a Nigerian tertiary health facility and the adaptations made during and after the population quarantine period.Methodology: A prospective and retrospective survey of all patients with orofacial cleft who had cleft surgeries, orthodontic interventions, and speech therapy in isolation or any of the combination was carried out. The survey period was divided into pre-COVID-19 lockdown period, the COVID-19 lockdown period, and the post-COVID-19 lockdown period with each of the periods spanning 4 months. The data which include: number of cleft clinic attendance, number of cleft surgical procedures, orthodontic interventions, and speech therapy session were retrieved from patients' case records in the cleft and orthodontic clinics. The data was also reported for each period and represented as numbers and percentages. The trend of cleft services was plotted as line graphs and the impact of the COVID-19 pandemic on cleft care services is said to be significant when P value is <.005.Result: During the COVID-19 Lockdown period, there was a 66% drop in level of cleft clinic attendance, 78% drop in cleft surgeries, 78% drop in Orthodontic interventions, and a 58% drop in the number of Speech Therapy sessions. After the Lockdown period, the clinic attendance increased by a 190%, cleft surgeries rose by more than 10-fold, and the orthodontic interventions increased 10-fold. The speech therapy sessions dwindled further by 6% during the post-COVID-19 Lockdown period. The drop in cleft care service during the study period was significant ( P = .001). The post Lockdown surge in cleft care services was also statistically significant ( P = .001).Conclusion: The COVID-19 pandemic significantly altered the volume of cleft care services but also with a significant rebound post-lockdown period.